To the problems of health management in the context of decentralization of power and spatial planning in the united territorial communities - Yanchuk, A. O.; Kuznichenko, S. O.; Okolovych, M. Ye. (Zaporozhye Medical Journal, 2018)
The purpose of the study is to determine the main factors that may adversely affect the spatial planning of the united territorial communities in the management of the healthcare industry. The reform of the administrative-territorial system of Ukraine provides for the creation of a new model of the territorial organization of power, decentralization of tasks, powers and responsibilities, development of the system of local self-government and formation of self-sufficient territorial communities, improvement of the state regional policy, etc. Considering that public health is one of the main factors in achieving national security and welfare of the state as a whole, it is urgent to introduce new approaches to solve public health problems. The functionality of direct management requires the creation of a special executive body with the powers of the budget holder, which can manage the medical subventions allocated for health and the implementation of measures for optimization of the network of healthcare institutions. Providing a medical institution of the basic level status of a legal entity will open the way for receiving its license to conduct medical practice. It is necessary to adopt special laws, which establish principles of administrative and territorial structure of Ukraine, to define the powers of executive authorities and local self- government at all levels in this field.